The Sublime is What Forces Us to Think. How the Kantian sublime informs the genesis of thought in Deleuze (Itinera, 2021)
Although Deleuze has written a whole volume on Kant, in the present essay I am paying close attention to a short and concentrated article of his on Kant’s third Critique entitled, The Idea of Genesis in Kant’s Aesthetic, because in it Deleuze highlights how the sublime experience is conducive to the aesthetic ought in Kant’s architectonic system, and how the sublime experience is necessary to engender artistic creativity. I argue, that although Deleuze rejects Kant’s thesis that there should be universal rules which determine thinking, he does take up Kant’s ideas of there being various mental faculties or capacities, which need to work together to produce all forms of thought and creative output. The possible disharmony of the distinct faculties, the violence that one might commit over the other, as happens in Kant’s sublime experience, becomes the violence in Deleuze’s philosophy which engenders creativity and, ultimately, forces one to think.
Keywords: Kant, Deleuze, faculties, creativity.